2015
DOI: 10.1177/0887403415607049
|View full text |Cite
|
Sign up to set email alerts
|

Compensating the Innocent: Perceptions of Exonerees’ Deservingness to Receive Financial Compensation for Wrongful Convictions

Abstract: Those who have been wrongfully imprisoned face a variety of challenges upon reentering the community, and monetary compensation may be helpful in rebuilding one's life following a period of incarceration. However, very little is known about factors that may impact public attitudes regarding compensation policy. Using a sample of 396 university students, we investigated the role of exonerees' race/ ethnicity and prior conviction history, as well as participants' socially dominant and right-wing authoritarian at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 46 publications
3
23
0
1
Order By: Relevance
“…Study participants cited justifications for compensation such as correcting a governmental wrong, starting their lives over, and lost wages. Another study using a larger sample of nearly 400 participants in the USA similarly found that the majority of participants supported compensation for exonerees; moreover, participants who were male, members of a minority group and older rated exonerees as most deserving of compensation (Karaffa et al, 2015).…”
Section: Compensationmentioning
confidence: 95%
“…Study participants cited justifications for compensation such as correcting a governmental wrong, starting their lives over, and lost wages. Another study using a larger sample of nearly 400 participants in the USA similarly found that the majority of participants supported compensation for exonerees; moreover, participants who were male, members of a minority group and older rated exonerees as most deserving of compensation (Karaffa et al, 2015).…”
Section: Compensationmentioning
confidence: 95%
“…That 14 states have no compensation laws at all is shameful, adding further injury to that already borne by exonerees. There is widespread support for government compensation of all wrongfully convicted individuals, yet little in terms of research into exactly how much compensation should be given (Clow et al, 2012;Clow & Ricciardelli, 2014;Karaffa et al, 2015). The current research surveyed students and laypersons in order to help explain how the current state of compensation statutes compares to what individuals feel is "fair compensation" for exonerees.…”
Section: Imentioning
confidence: 98%
“…There are potentially expected differences in exactly who supports compensation for exonerees based on individuals' gender, minority status, age, and political affiliation (Karaffa et al, 2015;Hicks et al, 2021). There are few known studies that directly look at how much compensation exonerees deserve.…”
Section: B Surveys Of Wrongful Convictionsmentioning
confidence: 99%
“…Weiner and colleagues (Weiner, ; Weiner, Osborne, & Rudolph, ; Weiner, Perry, & Magnusson, ) have found that people show less pity, more anger, and less altruism toward stigmatized individuals who are seen as responsible for their stigma (e.g., less willingness to assist a person who contracted AIDS via unprotected sex as opposed to a contaminated blood transfusion). Similarly, Karaffa, Page, and Koch () found that people rated exonerees as less deserving of financial restitution for their wrongful conviction if they had a prior and unrelated misdemeanor conviction.…”
Section: Introductionmentioning
confidence: 94%
“…Although 33 US states guarantee exonerees some amount of financial restitution (http://www.innocenceproject.org; see also Norris, ; Simms, ), many exonerees seek restitution in civil court, leaving a jury to decide how much compensation they deserve. Despite apparent public support for compensating exonerees (Clow, Blandisi, Ricciardelli, & Schuller, ; Karaffa et al, ), these lawsuits have had mixed outcomes: while some exonerees have won enormous awards, others who are equally deserving have won no compensation whatsoever (Bernhard, ). Perhaps exonerees who receive greater blame for their conviction (e.g., false confessors) tend to receive smaller damage awards, or none at all.…”
Section: Introductionmentioning
confidence: 99%